SEJARAH PERKEMBANGAN ISLAM DI LAOS: SUDUT PANDANG SEJARAH POLITIK - Tubagus, Najwa (Program Studi Sejarah Peradaban Islam Fakultas Ushuluddin Adab dan Dakwah IAIN Manado, 2024)
Muslim are the minority religion in Laos while Buddhism is the religion. The Muslims in Laos come from various regions ranging from from Cambodia there are ethnic Cham from China, Pakistan, and Tamil. This article aims to provide information understanding to readers to get to know Islam in the Indo-China region, especially Laos. Indo-China region, especially the country of Laos. This research uses a qualitative qualitative method with the historical method with four stages, namely heuristics, source criticism, interpretation, and historiography. source, interpretation, and historiography. The results of this study indicate that The process of the entry of Islam in Laos has several theories or opinions, each of which has Muslim communities from the region. theory there are Muslim communities from other regions that brought it. brought it. The Muslims in Laos many live in Vientiane, and they generally trade. And they coexist with the Buddhist community in a harmonious relationship, after the 1991 Constitution of the Lao People's Democratic Republic, which was amended in 2003, provided for freedom of religion and it was this provision that made Islam a legitimate presence.